2003
DOI: 10.1248/bpb.26.1574
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effects of Korean Ginseng Saponins on Ovarian Function in Immature Rats

Abstract: Superovulation induction with exogenous gonadotropins such as pregnant mare serum gonadotropin (PMSG) and human menopausal gonadotropin (hMG) is a well-established practical technique. The purpose of this technique is to achieve enhanced commercial production of genetically meritorious individuals in the livestock industry, to retrieve a number of oocytes and early embryos in various research fields including genetic engineering, and to treat medically diverse types of female infertility in human. In spite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
(34 reference statements)
0
15
1
Order By: Relevance
“…These results were in agreement with those reported by Shelby (2004). Although no significant effects were noticed in the animals that received Phoenix ginseng, the combined treatment succeeded in restoring the hormonal levels towards the normal values of the controls and provides strong evidence that Phoenix ginseng has a curative effect on ovarian dysfunction (Yu et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…These results were in agreement with those reported by Shelby (2004). Although no significant effects were noticed in the animals that received Phoenix ginseng, the combined treatment succeeded in restoring the hormonal levels towards the normal values of the controls and provides strong evidence that Phoenix ginseng has a curative effect on ovarian dysfunction (Yu et al, 2003).…”
Section: Discussionmentioning
confidence: 73%
“…A few studies have reported the action of ginsenosides on reproduction. Ginsenosides ameliorated ovarian dysfunction caused by excessive stimulation with equine chorionic gonadotropin in immature rats (Yu et al, 2003). Ginsenosides stimulated meiotic maturation of mouse oocytes through a paracrine pathway involving the nitric oxide/inducible nitric oxide synthase system .…”
Section: Introductionmentioning
confidence: 94%
“…Ginseng (Panax ginseng C.A. Meyer) has been regarded as one of the important remedies in oriental medicine for more than thousand years [2]. The objective of this work was to determine the shifts on the PCR-DGGE profiles of bacterial communities associated with the rhizosphere soil of ginseng at varying age levels.…”
Section: Introductionmentioning
confidence: 99%